Immunomodulatory effects of betulinic acid isolation from the bark of Melaleuca cajuputi - Abd Rahman, Mashitoh; Yeap, Swee Keong; Ali, Abdul Manaf; Ahmad, Faujan; M., Suhaimi; Ng, M. K.; Lam, H. Y.; Mohamed Alitheen, Noorjahan Banu (Universiti Putra Malaysia Press, 2012)
Betulinic acid and its derivatives showed cytotoxicity against variety of tumour and cancer cell lines comparable to some clinically used drug. In the present study, the immunomodulatory effects of betulinic acid, isolated from the roots of Melaleuca Cajuputi, was studied. Immunomodulatory effect was evaluated by using lymphocytes proliferation assay on mice splenocytes, thymocytes and human peripheral blood mononuclear cells (PBMC), while the cell cycle progression of betulinic acid treated PBMC was also studied by using flow cytometer. The production of human interleukin-2 (IL-2) and human inteleukin-12 (IL-12) cytokines was also assessed using enzyme-linked immunosorbent assay (ELISA). The results showed that betulinic acid was able to stimulate the proliferation of mice thymocytes, splenocytes and human PBMC in a time and dose-dependent manner. Meanwhile, betulinic acid treated immune cells were proliferated well at lower concentration (7.5 µg /mL), but growth inhibition occurred at a higher concentration (30 µg /mL). The findings obtained from the cell cycle analysis exhibited the proliferation effect of betulinic acid on PBMC, whereby 43.66 ± 2.60% and 42.83 ± 2.40% of the cells entered G2/M phase after 24h and 48h, respectively. Moreover, betulinic acid also induced extracellular IL-2 and IL-12 production. This finding demonstrates that betulinic acid acts as an immunomodulatory agent that may be useful in enhancing immune system.